Causal pathways linking polycystic ovary syndrome to distinct breast cancer subtypes through mediator factors: a multivariable mendelian randomization analysis - Runxiang Cao; Lanlan Chen; Yutong Liu; Xuyutian Wang; Ruolin Ma; Qian Zhao; Ye Du (BMC, 2023)
Abstract Polycystic ovary syndrome (PCOS) is an endocrine disorder characterized by ovarian cysts, high androgen levels, and irregular menstruation. The causality between PCOS and breast cancer (BC) has been widely discussed as they share a significant intersection in clinical manifestations. Previous epidemiological studies have not provided consistent conclusions in association between PCOS and BC, while mendelian randomization (MR) analyses have confirmed the causality between PCOS and estrogen receptor-positive breast cancer (ER + BC), but among a series of clinical manifestations resulting from PCOS, which related traits mediate the causal effect remains unknown. In this study, we conducted multivariable mendelian randomization (MVMR) analysis to explore the potential mediator variables in the mechanism linking PCOS to distinct subtypes of BC, and calculated the mediating effects proportion. We analyzed 13 PCOS-related traits and found that age at menopause may mediate PCOS-induced ER + BC (with -4.82% proportion) with a weak protective effect through the repair of DNA double-strand breaks by homologous recombination. This study helps to better comprehend the shared mechanisms contributing to the development of both PCOS and BC, and to screen high-risk populations for BC and take appropriate preventive measures.